PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERBUATAN MAIN HAKIM SENDIRI DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Prillicia, Sheren; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
As a stat of law, it is appropriate that the principles of a rule of law must be respected nd upheld, one of the principles is justice, which is the most central idea and at the same time the highest goal taught by every religion and humanity. The act of vigilantism is nothing but the act of exercising rights according to one’s own will which is arbitrary without the consent of other interested parties. In this case related to the vigilante case that occurred in the city of Pekanbaru.The purpose of writing this thesis,namely first to find out the law enforcement against criminal acts of vigilantism in the Pekanbaru district police jurisdiction. Second, to find out the factors causing the criminal acts of vigilante in the Pekanbaru district police jurisdiction. This type of research that wants to ee correlation between law and society, this research was conducted at the Pekanbaru city police department, while the population and sample are all parties related to the problem under study, in this study the sources of data use are primary data, secondary data, and tertiary data, data collection techniques in this study with interviews and literature studies.From the results of the research problem there are two main things that can be concluded. First, law enforcement against vigilantism in the city of Pekanbaru continues to be done by the victim making a report to the police so that the case can be processed, the obstacles faced in law enforcement are the people who do not immediately report, the evidence at the scene of the case, and the society that tends to cover each other. Secondly, the factors causing criminal act of vigilance in the city of Pekanbaru are social feelings and a sense of vigilante. The author suggestion, first is expected to the public to hand over the perpetrators suspected of committing crimes to the authorities nd not to commit vigilantism, secondly there is a need for socialization to the public that igilante conduct is probihitied and includes criminal offense that can be subject for those who commit them.Keywords: Law Enforcement – Criminal Act - Vigilantism